Development of three vitrification-based cryopreservation procedures for shoot tips of China's potato - Wang, B; Wang, R R; Li, J W; Ma, Y L; Sheng, W M; Li, M F; Wang, Q C (Cryo-Letters, 2013)
China is now the largest potato producing country worldwide. The establishment of efficient conservation techniques for potato germplasm is a prerequisite for breeding of elite cultivars. Potato viral diseases have been a great threat for sustainable potato production in China. Use of virus-free seed tubers is an effective and practical means to control viral diseases. In the present study, three vitrification-based cryopreservation techniques, i.e. droplet-vitrification, encapsulation-vitrification and vitrification were successfully developed for the first time for China's potato. Cultivar 'Zihuabai' was used to optimize key parameters involved in the three vitrification-based procedures. With the optimized parameters, shoot regrowth percentages of 71%, 76% and 43% were obtained for droplet-vitrification, encapsulation-vitrification and vitrification, respectively. The three protocols developed were further tested with eight China's major cultivars, with average shoot regrowth of 61%, 38% and 28% for droplet-vitrification, encapsulation-vitrification and vitrification, respectively. Successful development of the three cryopreservation procedures using a single cultivar will facilitate a number of comparative studies such as cryo-injury, regrowth pattern, genetic stability and efficiency of virus elimination. Testing these three cryogenic procedures for potato major cultivars representing a wide range of genetic background, will help the establishment of potato cryobanking in China and the production of virus-free plants.